A novel route towards water-soluble luminescent iridium(iii) complexes via a hydroxy-bridged dinuclear precursor. Issue 43 (7th October 2016) - Scarpelli, Francesca; Ionescu, Andreea; Ricciardi, Loredana; Plastina, Pierluigi; Aiello, Iolinda; La Deda, Massimo; Crispini, Alessandra; Ghedini, Mauro; Godbert, Nicolas
Abstract : The reactivity of[(ppy) 2 Ir(μ-OH)] 2 is described; a useful precursor to a series of luminescent water soluble ionic Ir(iii ) complexes with self-assembling properties. Abstract : The synthesis and photophysical characterization of a new family of luminescent water-soluble ionic iridium(iii ) complexes of the general formula[(ppy) 2 Ir(bpy)]X are reported. The Ir(iii ) complexes incorporate a cyclometalated 2-phenylpyridine (ppy ), the ancillary ligand 2, 2′-bipyridyl (bpy ) and different counterions (X − = EtO −, OH −, EtOCH2 CO2 −, MeOCH2 CO2 − ). These complexes were obtained starting from the cyclometalated Ir(iii ) chloro-bridged dimer[(ppy) 2 Ir(μ-Cl)] 2, for the first time synthesized through a new microwave assisted synthetic procedure, and subsequently converted into the corresponding hydroxy-bridged dimer[(ppy) 2 Ir(μ-OH)] 2 . The latter was eventually used as a sole reagent for the synthesis of all the reported complexes by simply varying the nature of the reaction solvent from water to alcohols and glycol ethers. This study demonstrates the versatility of the[(ppy) 2 Ir(μ-OH)] 2 complex as a precursor to water soluble ionic Ir(iii ) complexes. Indeed, [(ppy) 2 Ir(μ-OH)] 2 has shown its peculiar chemical reactivity due to both a strong base character and an unexpected oxidative ability towards the alcoholic function of glycol ethers. All the synthesized complexes exhibit, in water solution, an orange emission centred at 606 nm. Moreover, all complexes display the ability to give rise to gel phases in water upon increasing their concentration, and the photophysical study evidenced the various interactions governing the gelification process. The water-solubility of these new luminescent Ir(iii ) complexes makes them potentially useful in bio-related systems.